Post-lumpectomy CT-guided tumor bed delineation for breast boost and partial breast irradiation: Can additional pre- and postoperative imaging reduce interobserver variability? - DEN HARTOGH, MARISKA D. (Oncol Lett, 2015)
For breast boost radiotherapy or accelerated partial breast irradiation, the tumor bed (TB) is delineated by the radiation oncologist on a planning computed tomography (CT) scan. The aim of the present study was to investigate whether the interobserver variability (IOV) of the TB delineation is reduced by providing the radiation oncologist with additional magnetic resonance imaging (MRI) or CT scans. A total of 14 T1-T2 breast cancer patients underwent a standard planning CT in the supine treatment position following lumpectomy, as well as additional pre- and postoperative imaging in the same position. Post-lumpectomy TBs were independently delineated by four breast radiation oncologists on standard postoperative CT and on CT registered to an additional imaging modality. The additional imaging modalities used were postoperative MRI, preoperative contrast-enhanced (CE)-CT and preoperative CE-MRI. A cavity visualization score (CVS) was assigned to each standard postoperative CT by each observer. In addition, the conformity index (CI), volume and distance between centers of mass (dCOM) of the TB delineations were calculated. On CT, the median CI was 0.57, with a median volume of 22 cm(3) and dCOM of 5.1 mm. The addition of postoperative MRI increased the median TB volume significantly to 28 cm(3) (P<0.001), while the CI (P=0.176) and dCOM (P=0.110) were not affected. The addition of preoperative CT or MRI increased the TB volume to 26 and 25 cm(3), respectively (both P<0.001), while the CI increased to 0.58 and 0.59 (both P<0.001) and the dCOM decreased to 4.7 mm (P=0.004) and 4.6 mm (P=0.001), respectively. In patients with CVS≤3, the median CI was 0.40 on CT, which was significantly increased by all additional imaging modalities, up to 0.52, and was accompanied by a median volume increase up to 6 cm(3). In conclusion, the addition of postoperative MRI, preoperative CE-CT or preoperative CE-MRI did not result in a considerable reduction in the IOV in postoperative CT-guided TB delineation, while target volumes marginally increased. The value of additional imaging may be dependent on CVS.